Solution‐Processable Anode Double Buffer Layers for Inverted Polymer Solar Cells. Issue 8 (11th March 2020) - Cominetti, Alessandra; Serrano, Giulia; Savoini, Alberto; Carbonera, Chiara; Melchiorre, Fabio; Perucchini, Sara; Congiu, Annalisa; Corso, Gianni; Barbieri, Riccardo; Trippodo, Elisa; Caneschi, Andrea; Po, Riccardo
Abstract : Although organic solar cells have surpassed the 17% power conversion efficiency threshold, commercial modules efficiencies are only around 4–5%. One of the reason is the lack of effective solution‐processable hole transport materials that are a key element for the scale‐up on roll‐to‐roll printing equipments and the commercial development. Herein, a class of novel vanadium and molybdenum polyoxometallate salts are developed that, alone or in combination with a traditional poly(ethylene‐3, 4‐dioxytiophene):poly(styrene sulfonate) (PEDOT:PSS) layer, can be used as anodic buffer layer in inverted polymer solar cells. These materials exhibit work function values around 5.8 eV that match well with highest occupied molecular orbital energies of typical polymer donors. They are tested with different widely used active systems, including PTB7:PC71BM, PV2000:PCBM, and PffBT4T:PC71BM. Vanadium and molybdenum polyoxometallate can be deposited from solutions and, contrary to PEDOT:PSS used alone, do not cause a drop of performances compared with evaporated molybdenum oxide (e‐MoO x ); on the contrary, in the best cases they achieve similar performances to e‐MoO x . Slot‐die‐coated PV2000:PCBM solar cells on flexible substrate achieve a remarkable power conversion efficiency of almost 7.6%. Abstract : Vanadium and molybdenum polyoxometallate salts, in combination with poly(ethylene‐3, 4‐dioxytiophene):poly(styrene sulfonate) (PEDOT:PSS), are efficient hole transport layer for inverted polymer solar cells, avoiding the drop of photovoltaic performances observed when PEDOT:PSS is used alone. PV2000:PCBM slot‐die‐coated flexible solar cells, with molybdenyl phosphomolybdate/PEDOT:PSS anode buffer layer, achieve a maximum power conversion efficiency of 7.6%.